Optical Fibre-Based Sensors for Oil and Gas Applications - Jincy Johny; Solomon Amos; Radhakrishna Prabhu (Sensors, 2021)
Oil and gas (O&G) explorations moving into deeper zones for enhanced oil and gas recovery are causing serious safety concerns across the world. The sensing of critical multiple parameters like high pressure, high temperature (HPHT), chemicals, etc., are required at longer distances in real-time. Traditional electrical sensors operate less effectively under these extreme environmental conditions and are susceptible to electromagnetic interference (EMI). Hence, there is a growing demand for improved sensors with enhanced measurement capabilities and also sensors that generates reliable data for enhanced oil and gas production. In addition to enhanced oil and gas recovery, the sensing technology should also be capable of monitoring the well bore integrity and safety. The sensing requirements of the O&G industry for improved sensing in deeper zones include increased transmission length, improved spatial coverage and integration of multiple sensors with multimodal sensing capability. This imposes problems like signal attenuation, crosstalks and cross sensitivities. Optical fibre-based sensors are expected to provide superior sensing capabilities compared to electrical sensors. This review paper covers a detailed review of different fibre-optic sensing technologies to identify a feasible sensing solution for the O&G industry.